ChemInform Abstract: Acyclic Sulfides, Garlicnins L‐1—L‐4, E, and F, from Allium sativum. Issue 44 (4th November 2014) - Nohara, Toshihiro; Fujiwara, Yukio; Ikeda, Tsuyoshi; Yamaguchi, Koki; Manabe, Hideyuki; Murakami, Kotaro; Ono, Masateru; Nakano, Daisuke; Kinjo, Junei
Abstract Six novel acyclic sulfides, named garlicnins L‐1 (I), L‐2, L‐3, L‐4 (II), E (III) and F are isolated which are able to suppress M2 macrophage activation.